Gradient aerogel framework with low-reflection electromagnetic shielding performance and preparation method and application thereof
The electromagnetic shielded aerogel framework with concentration gradient and pore gradient structures was prepared through 3D printing technology, which solved the problems of high reflectivity and cumbersome preparation process of traditional materials, achieved efficient electromagnetic shielding and low reflection characteristics, and had multi-scene adaptability and excellent photothermal conversion performance.
Patent Information
- Application Number
- CN202510375099.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-06-17
AI Technical Summary
While improving the electromagnetic shielding efficiency, traditional electromagnetic shielding materials often lead to high reflectivity, causing secondary electromagnetic radiation pollution, and the preparation process is cumbersome and uncontrollable.
An electromagnetic shielded aerogel framework with concentration gradient and pore gradient structures was prepared using 3D printing technology. It was composed of cellulose nanofibers, MXene and poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid in different proportions. Each step of the gradient structure is composed of different proportions of materials, combining the flexibility and controllability of 3D printing.
It achieves ultra-high gigahertz total electromagnetic shielding efficiency, while maintaining excellent low reflection characteristics, and has excellent heterogeneous photothermal conversion performance. It is suitable for multi-scene electromagnetic shielding, infrared camouflage and military communication fields.
Smart Images

Figure CN120157949A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of materials. Specifically, it relates to an aerogel framework with low-reflection electromagnetic shielding performance and having a concentration gradient and a pore gradient structure, and a preparation method thereof. By using 3D printing technology, the gradient aerogel framework prepared by this method has an ultra-high total electromagnetic shielding efficiency in gigahertz and at the same time maintains excellent low-reflection characteristics, and also has excellent heterogeneous photothermal conversion performance, and has great application potential in fields such as multi-scenario adaptable electromagnetic shielding composite materials, high-temperature stealth and anti-freezing materials, and military communications. Background Art
[0002] Electromagnetic interference shielding technology is based on specific materials or structures to block, absorb or reflect external electromagnetic waves, thereby effectively preventing electromagnetic interference and protecting the equipment and human health. Traditional shielding strategies mainly rely on selecting highly conductive materials to achieve high electromagnetic shielding efficiency, but this usually results in an electromagnetic wave reflectivity of over 90%, and causes serious secondary electromagnetic radiation pollution. Therefore, it is necessary to develop absorption-guided shielding materials with low reflectivity to create a safer electromagnetic environment. Although low-conductivity materials can enhance the impedance matching between electromagnetic waves and air and promote the absorption of more electromagnetic waves, this often leads to a reduction in the total electromagnetic shielding efficiency. Therefore, there is an urgent need to find a design strategy that balances high electromagnetic shielding efficiency and low reflection characteristics. In recent years, more and more researchers have been committed to studying electromagnetic shielding composites with high electromagnetic shielding effectiveness using various preparation methods for shielding electromagnetic waves. For example, Han et al. proposed using chemical vapor deposition method and carbon hetero-stacking strategy to construct a fully carbon electromagnetic shielding aerogel for epoxy resin modification (L.Y. Han, K.Z. Li, H.M. Liu, Y.M. Jiao, X.M. Yin, H.J. Li, Q. Song, L.H. Qi, Chem. Eng. J. 2023, 465, 142839); Jiang et al. prepared lightweight hafnium carbide nanowire (HfCnw)-carbon fiber (CF) / graphene aerogel (GA) composites with excellent electromagnetic shielding performance by introducing carbon fiber (CF) and chemical vapor infiltration pyrolytic carbon (PyC) coating through hydrothermal method (D.X. Jiang, S. Tian, H.J. Li, Z.W. Du, T. Liu, D.K. Yan, L. Zhou, S. Bai, X.F. Qiang, Carbon. 2024, 219, 118788); Wan et al. prepared a good electromagnetic interference shielding ability hybrid aerogel composed of graphene oxide (GO) and cellulose through solution mixing-regeneration-freeze drying process (C.C. Wan, J. Li, Carbohydr. Polym. 2016, 150, 172-179); These electromagnetic shielding materials all have good shielding effects, but the above-mentioned several preparation processes are cumbersome and uncontrollable, which limits their applications. 3D printing technology can accurately construct macroscopic and microscopic nanostructures and various shapes, etc., and has good application prospects in the fields such as electromagnetic interference shielding, with design flexibility, cost-effectiveness, controllability and reproducibility.To address these issues, Qi et al. developed an aqueous MXene / sodium alginate ink to prepare aerogel grids with customized geometries using 3D printing, which have ultra-high electrical conductivity, excellent mechanical properties, and excellent electromagnetic shielding effectiveness (C.Z. Qi, X.Y. Wu, J. Liu, X.J. Luo, H.B. Zhang, Z.Z. Yu, J MATER SCI TECHNOL. 2023, 135, 213-220). However, there is still a significant electromagnetic wave reflection problem.
[0003] However, the above traditional effective shielding strategies mainly rely on the reflection effect, which will inevitably lead to poor impedance matching and excessive electromagnetic wave reflection, resulting in serious secondary electromagnetic radiation pollution and being unfavorable for the development of new green and environmentally friendly electromagnetic interference shielding materials. Future shielding materials still need to meet the requirements of low reflection characteristics, lightweight multi-scenario adaptability, electromagnetic high-temperature stealth, anti-freezing, and resistance to harsh environments to meet the strict requirements of next-generation shielding applications. Summary of the Invention
[0004] Aiming at the problems of traditional methods, the purpose of the present invention is to provide an electromagnetic shielding aerogel framework with low-reflection electromagnetic shielding performance and simultaneously having a concentration gradient and a pore gradient, as well as its preparation method and uses. The aerogel framework has a multi-stage concentration gradient and a pore gradient in the thickness direction, not only having an ultra-high total electromagnetic shielding efficiency in gigahertz, but also maintaining excellent low-reflection characteristics. The preparation method of the aerogel framework uses 3D printing technology, making the preparation method have application flexibility, adaptability, and customizability to meet large-scale preparation and industrialization. In addition, the aerogel also has excellent photothermal conversion ability, enabling multi-scenario adaptive applications, such as de-icing, infrared camouflage of high-temperature equipment, and infrared camouflage of false targets, etc., thereby effectively protecting the equipment in military exploration. The above characteristics make it have great application potential in the fields of multi-scenario adaptable electromagnetic shielding composite materials, high-temperature stealth and anti-freezing materials, and military communications.
[0005] According to one aspect of the present invention, an object of the present invention is to provide an electromagnetic shielding aerogel framework having a concentration gradient and a pore gradient structure. The aerogel framework has a multi-stage concentration gradient and a pore gradient structure in the thickness direction. Each stage of the gradient structure of the aerogel framework is composed of different proportions of cellulose nanofibers (CNFs), MXene, and poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate (PEDOT:PSS).
[0006] Preferably, the multi-stage concentration gradient and pore gradient of the aerogel framework are at least 3-stage gradient structures.
[0007] Preferably, in the three-level gradient of the aerogel framework, in each concentration gradient from bottom to top in the thickness direction, the content ratio of MXene and cellulose nanofibers remains the same, while the content of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid is different. The weight ratio of cellulose nanofibers:MXene:(PEDOT:PSS) is 1:8:1.5 to 1:8:4, 1:8:0.5 to 1:8:1.2, 1:8:0 to 1:8:0.1, preferably 1:8:1.8 to 1:8:2.2, 1:8:0.8 to 1:8:1.1, 1:8:0 to 1:8:0.05, and more preferably 1:8:2, 1:8:1, 1:8:0. Here, 1:8:0 means no PEDOT:PSS is added.
[0008] Preferably, in the three-level gradient of the aerogel framework, in each pore gradient from bottom to top in the thickness direction, they are 0.8 to 2.0 mm, 0.3 to 0.7 mm, 0.05 to 0.25 mm respectively, preferably 0.8 to 1.5 mm, 0.45 to 0.65 mm, 0.10 to 0.20 mm, and more preferably 1.0 mm, 0.6 mm, 0.2 mm.
[0009] Preferably, the cellulose nanofibers are purchased from Tianjin Wood Elf Technology Co., Ltd., with the model number TOCNF-PL-2.
[0010] According to another aspect of the present invention, an object of the present invention is to provide a preparation method of the electromagnetic shielding aerogel framework having a concentration gradient and a pore gradient structure. The preparation method is based on 3D printing technology and includes the following steps:
[0011] 1) Prepare MXene precipitate
[0012] Dissolve 1 part by weight of LiF in 20 parts by weight of 9M hydrochloric acid, then add 1 part by weight of Ti3AlC2 powder, and stir at 35 °C for 48 h; the suspension obtained after the reaction is centrifuged at 3500 r / min for 5 min, washed with deionized water until the pH of the supernatant is ≥ 5, and the supernatant is poured out; the obtained multi-layer MXene compound precipitate is dispersed and added to 25 parts by weight of deionized water, sonicated in an ice bath for 1 h, then centrifuged at 3500 r / min for 60 min, and the bottom MXene precipitate is recovered and concentrated, and centrifuged at a high speed of 10,000 r / min for 1 h to obtain the MXene precipitate;
[0013] 2) Prepare poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS)
[0014] Under stirring conditions, 2 parts by weight of poly(sodium 4-styrenesulfonate) and 2 parts by weight of 3,4-ethylenedioxythiophene were added to 400 parts by weight of deionized water, and stirred at room temperature for 15 min. Then, 5 parts by weight of sodium persulfate and 0.01 part by weight of anhydrous ferric chloride were slowly added to the above mixture to initiate polymerization, and stirred thoroughly in an ice bath for 24 h. As the reaction proceeded, the mixture changed from light blue to dark blue. After the reaction was terminated, the liquid was washed 3 times with a water / methanol mixture in a volume ratio of 1:1 to remove unreacted 3,4-ethylenedioxythiophene, and then washed 3 times with deionized water. The obtained sediment was placed at -4 °C for freezing, and then freeze-dried in a vacuum freeze dryer at -48 °C and a vacuum degree of 20 Pa to obtain PEDOT:PSS powder;
[0015] 3) Preparation of 3D printing ink
[0016] 5 parts by weight of the MXene precipitate with a weight percentage of 22.4% obtained in the above step 1) was added to 14 parts by weight of cellulose nanofibers with a weight percentage of 1% in a mortar and ground evenly. The PEDOT:PSS powder was redispersed with a deionized water / dimethyl sulfoxide mixture with a volume ratio of 85:15. Then, the PEDOT:PSS powder was added to the above mixture at a weight ratio of cellulose nanofibers:MXene:(PEDOT:PSS) of 1:8:0, 1:8:1, and 1:8:2 respectively and ground thoroughly to form 3D printing ink, where 1:8:0 means no PEDOT:PSS is added;
[0017] 4) Preparation of gradient electromagnetic shielding aerogel framework
[0018] The three kinds of mixed inks obtained in the above step 3) were loaded into a syringe and left to stand at room temperature to remove air bubbles. The required geometric patterns for printing were pre-designed and drawn by computer-aided design software (CAD). The movement path file of the printer nozzle was exported through Autotesk ArtCAM2017 slicing software, and the data was imported into a direct writing 3D printer. Finally, the ink was extruded from the nozzle to form filaments, and stacked layer by layer through the three-axis control of the printer. The pore size was controlled by controlling the operating parameters of the 3D printer.
[0019] Preferably, the printing moving speed is preferably 16.5 - 22.5 mm / s, and more preferably 19.5 mm / s.
[0020] Preferably, the inner diameter of the printing nozzle is preferably 230 - 640 μm, and more preferably 460 μm.
[0021] Preferably, the extrusion feeding speed of the printing ink is preferably 14 - 18 mL / hr, and more preferably 16 mL / hr.
[0022] According to another aspect of the present invention, another object of the present invention is to provide a low-reflection electromagnetic shielding device, which is prepared from the electromagnetic shielding aerogel framework having a concentration gradient and a pore gradient structure according to the present disclosure.
[0023] Beneficial effects
[0024] 1. In the preparation method of the gradient electromagnetic shielding aerogel framework prepared according to the present invention, the 3D printing technology has flexibility, adaptability, customizability, and simplicity in preparation, and has a wide application range.
[0025] 2. The gradient electromagnetic shielding aerogel framework prepared according to the present invention has an ultra-high total electromagnetic shielding efficiency in the gigahertz band and also maintains excellent low-reflection characteristics. It shows an excellent electromagnetic shielding value of 106.43 dB and an ultra-low reflection shielding efficiency of 2.45 dB in the gigahertz band, and the reflection coefficient R reaches 0.42.
[0026] 3. The gradient electromagnetic shielding aerogel framework prepared according to the present invention shows good effects in actual simulated electromagnetic shielding tests, and has the possibility of adjustable size and large-scale production.
[0027] 4. The gradient electromagnetic shielding aerogel framework prepared according to the present invention has excellent photothermal properties, and can simultaneously achieve multi-scene adaptability such as de-icing, infrared stealth of high-temperature equipment, and infrared camouflage of false targets.
[0028] 5. The focus of the present invention is on the gradient structure of the electromagnetic shielding aerogel. This gradient structure design can minimize the reflection of incident waves, promote internal multiple reflections and absorptions, thereby generating a wide range of attenuation paths to dissipate the energy of electromagnetic waves and reduce secondary pollution caused by electromagnetic waves. Description of the drawings
[0029] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following will briefly introduce the drawings required for use in the description of the specific embodiments or the prior art. Obviously, the following drawings are some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.
[0030] Figure 1 It is a preparation flow chart of the electromagnetic shielding aerogel framework having a concentration gradient and a pore gradient structure according to the present invention.
[0031] Figure 2 It is an X-ray diffraction pattern of the gradient electromagnetic shielding aerogel framework, cellulose nanofibers, poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, and MXene precipitate prepared according to Example 1.
[0032] Figure 3 X-ray photoelectron spectroscopy analysis diagrams of the gradient electromagnetic shielding aerogel framework, poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, and MXene precipitate prepared according to Example 1.
[0033] Figure 4 Raman spectra of the gradient electromagnetic shielding aerogel framework and poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid prepared according to Example 1.
[0034] Figure 5 Transmission electron microscopy images of the MXene precipitate and cellulose nanofibers, and scanning electron microscopy images of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, prepared according to Example 1.
[0035] Figure 6 Flow chart for preparing the gradient electromagnetic shielding aerogel framework by 3D printing technology according to Example 1.
[0036] Figure 7 Scanning electron microscopy images of three pore gradients in the gradient electromagnetic shielding aerogel framework prepared according to Example 1.
[0037] Figure 8 Scanning electron microscopy cross-sectional images and energy spectrum diagrams of the gradient electromagnetic shielding aerogel framework prepared according to Example 1.
[0038] Figure 9 Test on the electromagnetic shielding performance of the gradient electromagnetic shielding aerogel framework prepared according to Examples 1-2.
[0039] Figure 10 Test on the electromagnetic shielding performance of the gradient electromagnetic shielding aerogel framework prepared according to Examples 3-4.
[0040] Figure 11 Test on the electromagnetic shielding performance of the gradient electromagnetic shielding aerogel framework prepared according to Examples 1, 3 and Comparative Example 1.
[0041] Figure 12 Experiment on the printing flexibility of the 3D printing ink prepared according to Example 1.
[0042] Figure 13 Test on the actual electromagnetic shielding simulation of the gradient electromagnetic shielding aerogel framework prepared according to Example 1.
[0043] Figure 14 Test experiment on the sunlight photothermal conversion performance and stability of the gradient electromagnetic shielding aerogel framework prepared according to Example 1.
[0044] Figure 15Test experiment on the 808 infrared laser photothermal conversion performance and stability of the gradient electromagnetic shielding aerogel framework prepared according to Example 1.
[0045] Figure 16 Infrared stealth experiment on de-icing and high-temperature equipment of the gradient electromagnetic shielding aerogel framework prepared according to Example 1. Detailed implementation manners
[0046] Hereinafter, the present invention will be described in detail. Before the description, it should be understood that the terms used in this specification and the appended claims should not be construed as limited to the general meaning and dictionary meaning, but should be interpreted according to the meanings and concepts corresponding to the technical aspects of the present invention on the basis of the principle that allows the inventor to appropriately define the terms for the best interpretation. Therefore, the description presented here is only a preferred example for illustrative purposes and is not intended to limit the scope of the present invention. Thus, it should be understood that other equivalent ways or improved ways can be obtained without departing from the spirit and scope of the present invention.
[0047] In this article, the terms "comprising", "including", "having", "containing" or any other similar terms are all open connectives, which are intended to cover non-exclusive inclusions. For example, a composition or article containing plural elements is not limited only to these elements listed herein, but may also include other elements that are not explicitly listed but are usually inherent in the composition or article. In addition, unless there is a clear contrary statement, the term "or" refers to an inclusive "or" rather than an exclusive "or". For example, any of the following situations satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), A and B are both true (or exist). In addition, in this article, the interpretations of the terms "comprising", "including", "having", "containing" should be regarded as having specifically disclosed and simultaneously covered closed or semi-closed connectives such as "consisting of..." and "substantially consisting of...".
[0048] In this article, all features or conditions defined in the form of numerical ranges or percentage ranges are only for the sake of brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be regarded as having covered and specifically disclosed all possible sub-ranges and individual numerical values within the range, especially integer numerical values. For example, the range description of "1 to 8" should be regarded as having specifically disclosed all sub-ranges such as 1 to 7, 2 to 8, 2 to 6, 3 to 6, 4 to 8, 3 to 8, etc., especially the sub-ranges defined by all integer numerical values, and should be regarded as having specifically disclosed individual numerical values such as 1, 2, 3, 4, 5, 6, 7, 8 within the range. Unless otherwise specified, the foregoing interpretation method applies to all contents of the present invention throughout the text, regardless of the breadth of the range.
[0049] If a quantity or other numerical value or parameter is expressed as a range, a preferred range, or a series of upper and lower limits, it should be understood that all ranges formed by any pair of the upper limit or preferred value of the range and the lower limit or preferred value of the range have been specifically disclosed herein, regardless of whether these ranges are separately disclosed. In addition, when a range of numerical values is mentioned herein, unless otherwise specified, the range should include its endpoints and all integers and fractions within the range.
[0050] A 3D printing-based electromagnetic shielding aerogel framework with a gradient structure prepared by the preparation method of the present invention has an ultra-high total electromagnetic shielding efficiency in the gigahertz range, while also maintaining excellent low reflection characteristics, and also has the ability of photothermal conversion and adaptability to multiple scenarios. Figure 1 It is a flowchart for the preparation of the gradient electromagnetic shielding aerogel framework according to the present invention.
[0051] In the aerogel framework according to the present invention, the concentration gradient of the aerogel framework from bottom to top is in a weight ratio of cellulose nanofibers:MXene:(PEDOT:PSS) of 1:8:1.5 to 1:8:4, 1:8:0.5 to 1:8:1.2, 1:8:0 to 1:8:0.1, preferably 1:8:1.8 to 1:8:2.2, 1:8:0.8 to 1:8:1.1, 1:8:0 to 1:8:0.05, more preferably 1:8:2, 1:8:1, 1:8:0. When the numerical value is in the concentration gradient of the aerogel framework from bottom to top, when the bottom layer concentration is less than or equal to the top layer concentration, due to the incident electromagnetic wave entering from the top layer of the aerogel framework, the high concentration and high conductivity lead to impedance mismatch, thereby enhancing reflection. When the bottom layer concentration is greater than the top layer concentration, the low concentration and low conductivity of the top layer make the electromagnetic wave impedance-matched between the air and the interface, reducing the reflection of the electromagnetic wave into the interior of the aerogel framework to occur multiple reflections and absorptions, thereby reducing reflection.
[0052] In the aerogel framework according to the present invention, in the three-level gradient of the aerogel framework, each pore gradient from bottom to top in the thickness direction is 0.8 to 2.0 mm, 0.3 to 0.7 mm, 0.05 to 0.25 mm, preferably 0.8 to 1.5 mm, 0.45 to 0.65 mm, 0.10 to 0.20 mm, more preferably 1.0 mm, 0.6 mm, 0.2 mm. In the pore gradient of the aerogel framework from bottom to top, when the bottom layer pores are greater than or equal to the top layer pores, due to the incident electromagnetic wave entering from the top layer of the aerogel framework, the small pores lead to impedance mismatch, thereby enhancing reflection. When the bottom layer pores are less than the top layer pores, the large pores of the top layer make the electromagnetic wave impedance-matched between the air and the interface, reducing the reflection of the electromagnetic wave into the interior of the aerogel framework to occur multiple reflections and absorptions, thereby reducing reflection.
[0053] In the aerogel framework according to the present invention, in the concentration and pore gradient from bottom to top of the aerogel framework, when the bottom layer concentration is less than or equal to the top layer concentration and the bottom layer pores are greater than or equal to the top layer pores, when the incident electromagnetic wave is incident from the top layer of the aerogel framework, the high concentration, high conductivity and small pores result in impedance mismatch, thus enhancing reflection. When the bottom layer concentration is greater than the top layer concentration and the bottom layer pores are less than the top layer pores, the low concentration, low conductivity and large pores in the top layer make the impedance match between the electromagnetic wave in the air and the interface, reducing the reflection of the electromagnetic wave into the interior of the aerogel framework to occur multiple reflections and absorptions, thus reducing reflection.
[0054] In the aerogel framework according to the present invention, the electromagnetic shielding aerogel framework has a gradient structure. When the electromagnetic shielding aerogel framework does not have a gradient structure, the impedance match between the air and the material interface is not well improved, resulting in the weakening of the electromagnetic wave reflection effect not being obvious.
[0055] Specifically, step 1) of preparing the MXene precipitate and step 2) of preparing poly(3,4-ethylenedioxythiophene)-polystyrenesulfonic acid according to the preparation method of the electromagnetic shielding aerogel framework are both conventional preparation methods, and are not limited to the methods defined in the invention content part of this application.
[0056] The aerogel framework has high conduction loss, dipole polarization loss ability, efficient absorption and multiple reflections of the incident wave, so it exhibits high electromagnetic shielding efficiency and effective anti-reflection performance. The relatively large pores and low conductivity at the top of the framework are more conducive to the incident wave entering the interior and optimizing the impedance match between the surface and free space, thus minimizing the reflection when the electromagnetic wave reaches the surface of the framework. The relatively small pores and high conductivity at the bottom of the framework electromagnetic wave have strong multiple reflections inside, dissipating the electromagnetic wave energy to the greatest extent, reducing the secondary electromagnetic radiation pollution, and reflecting the superiority of the gradient structure design.
[0057] The electromagnetic shielding gradient aerogel framework prepared according to the preparation method of the present invention has an ultra-high total electromagnetic shielding efficiency in gigahertz and also maintains excellent low reflection characteristics. On the premise that the reflection coefficient is 0.42 and the reflection value is 2.45 dB, its electromagnetic shielding ability in the gigahertz range can reach 106.43 dB.
[0058] The electromagnetic shielding gradient aerogel framework prepared according to the preparation method of the present invention has excellent photothermal conversion ability. Under the irradiation of 2 sunlights, the surface temperature can reach 70.1 degrees Celsius. Under the irradiation of an 808 infrared laser lamp with a power of 0.8 milliwatt per square centimeter, the surface temperature can reach 164.5 degrees Celsius.
[0059] The following examples are only listed as examples of the implementation of the present invention and do not constitute any limitation to the present invention. Those skilled in the art can understand that modifications within the scope of not deviating from the essence and concept of the present invention fall within the protection scope of the present invention. Unless otherwise specified, the reagents and instruments used in the following examples are commercially available products. The 3D printer used in this disclosure was purchased from Changsha Nano Instruments Co., Ltd., with the model number JDX02.
[0060] Example 1
[0061] 1) Preparation of MXene precipitate
[0062] Dissolve 1 g of LiF in 20 g of 9 M hydrochloric acid, then add 1 g of Ti3AlC2 powder and stir at 35 °C for 48 h; the suspension obtained after the reaction is centrifuged at 3500 r / min for 5 min, washed with deionized water until the pH of the supernatant is ≥5, and the supernatant is poured out; the obtained multi-layer MXene compound precipitate is dispersed and added to 25 g of deionized water, ultrasonically treated in an ice bath for 1 h, then centrifuged at 3500 r / min for 60 min, and the bottom MXene precipitate is recovered and concentrated, and centrifuged at a high speed of 10,000 r / min for 1 h to obtain the MXene precipitate.
[0063] 2) Preparation of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS)
[0064] Under stirring conditions, add 2 g of poly(4-styrenesulfonate sodium) and 2 g of 3,4-ethylenedioxythiophene to 400 g of deionized water and stir at room temperature for 15 min. Then slowly add 5 g of sodium persulfate and 0.01 g of anhydrous ferric chloride to the above mixture to initiate polymerization, and stir thoroughly in an ice bath for 24 h. As the reaction progresses, the mixture changes from light blue to dark blue. After the reaction is terminated, the liquid is washed 3 times with water / methanol in a volume ratio of 1:1 to remove unreacted 3,4-ethylenedioxythiophene, and then washed 3 times with deionized water. The obtained sediment is placed at -4 °C for freezing, and then freeze-dried in a vacuum freeze dryer at -48 °C and a vacuum degree of 20 Pa to obtain PEDOT:PSS powder.
[0065] 3) Preparation of 3D printing ink
[0066] Add the 5 g of MXene precipitate with a weight percentage of 22.4% obtained in step 1) above to 14 g of a 1% cellulose nanofiber solution in a mortar and grind evenly. Redisperse the PEDOT:PSS powder with a deionized water / dimethyl sulfoxide mixture with a volume ratio of 85:15, and then add the PEDOT:PSS powder to the above mixture at a weight ratio of cellulose nanofiber:MXene:(PEDOT:PSS) of 1:8:0, 1:8:1, and 1:8:2 respectively and grind completely to form 3D printing ink, where 1:8:0 means no addition of PEDOT:PSS;
[0067] 4) Prepare a gradient electromagnetic shielding aerogel framework
[0068] Load the three different content ratios of mixed ink obtained in step 3) above into different syringes and let them stand at room temperature to remove air bubbles. The inner diameter of the printing nozzle is 460 μm. The geometric patterns required for printing are pre-designed and drawn through computer-aided design software (CAD). The motion path file of the printer nozzle is exported through Autotesk ArtCAM2017 slicing software, and the data is imported into a direct writing 3D printer. Finally, the ink is extruded from the nozzle to form filaments and stacked layer by layer through the three-axis control of the printer. The printing moving speed is 19.5 mm / s, and the ink extrusion feeding speed is 16 mL / hr. The gradient electromagnetic shielding aerogel framework is divided into three gradients and realized from bottom to top by the printer. The concentration and pore gradients are 1:8:2, 1:8:1, 1:8:0 and 0.2 mm, 0.6 mm, 1.0 mm. The printed samples are all immersed in a calcium chloride solution, placed in a -4°C refrigerator for freezing, and then freeze-dried in a vacuum freeze dryer at a vacuum degree of -48°C and 20 Pa to obtain a gradient electromagnetic shielding aerogel framework.
[0069] As Figure 2 shown, the gradient electromagnetic shielding aerogel framework prepared in Example 1 was analyzed by X-ray diffraction pattern, and it can be seen that the diffraction peaks of each component of the gradient electromagnetic shielding aerogel framework are obvious, proving the successful preparation of the composite material.
[0070] As Figure 3 shown, X-ray photoelectron spectroscopy (XPS) was used to analyze the gradient electromagnetic shielding aerogel framework, poly(3,4-ethylenedioxythiophene)-polystyrenesulfonic acid and MXene precipitate prepared in Example 1, proving the successful synthesis of the material.
[0071] As Figure 4 shown, Raman spectroscopic characterization tests were carried out on the gradient electromagnetic shielding aerogel framework and poly(3,4-ethylenedioxythiophene)-polystyrenesulfonic acid prepared in Example 1, and it can be seen that there is a displacement of the obvious peaks, further proving the successful preparation of the composite material.
[0072] As Figure 5 shown, a transmission electron microscope (TEM) was used to characterize the MXene precipitate and cellulose nanofibers prepared in Example 1, and a scanning electron microscope (SEM) was used to analyze poly(3,4-ethylenedioxythiophene)
[0073] -polystyrene sulfonic acid, which proved the successful synthesis of the raw materials.
[0074] As Figure 7 shown, a scanning electron microscope (SEM) was used to characterize the gradient electromagnetic shielding aerogel framework prepared in Example 1, which proved the successful preparation of its gradient structure.
[0075] As Figure 8 shown, the gradient electromagnetic shielding aerogel framework prepared in Example 1 was subjected to energy spectrum testing by scanning electron microscopy, which proved the element distribution within its structure and the uniform mixing of the raw materials.
[0076] Figure 12 The 3D printing composite ink according to Example 1 can be seen that various two-dimensional or three-dimensional structures such as snake-shaped, honeycomb-shaped, pyramid-shaped, different-sized grid frameworks, and shielding elements of integrated boards can be prepared by printing the composite ink of Example 1 through 3D printing technology. It proves the application flexibility, adaptability, and customizability of 3D printing preparation technology.
[0077] Example 2
[0078] The printer parameters and printing steps were carried out according to Example 1. The gradient electromagnetic shielding aerogel framework was realized from bottom to top by the printer in three gradients, and the concentration and pore gradients were 1:8:0, 1:8:1, 1:8:2 and 1.0 mm, 0.6 mm, 0.2 mm. The printed samples were all immersed in calcium chloride solution, placed in a -4°C refrigerator for freezing, and then freeze-dried in a vacuum freeze-dryer at -48°C and a vacuum degree of 20 Pa to obtain the gradient electromagnetic shielding aerogel framework.
[0079] Example 3
[0080] The printer parameters and printing steps were carried out according to Example 1. The gradient electromagnetic shielding aerogel framework was realized from bottom to top by the printer in three gradients, and the concentration and pore gradients were 1:8:2, 1:8:1, 1:8:0 and 0.6 mm, 0.6 mm, 0.6 mm. The printed samples were all immersed in calcium chloride solution, placed at -4°C for freezing, and then freeze-dried in a vacuum freeze-dryer at -48°C and a vacuum degree of 20 Pa to obtain the gradient electromagnetic shielding aerogel framework.
[0081] Example 4
[0082] The printer parameters and printing steps are carried out according to Example 1. The gradient electromagnetic shielding aerogel framework is divided into three gradients and realized from the printer upwards. The concentration and pore gradients are 1:8:0, 1:8:1, 1:8:2 and 0.6 mm, 0.6 mm, 0.6 mm. The printed samples are all immersed in calcium chloride solution, placed in a refrigerator at -4°C for freezing, and then freeze-dried in a vacuum freeze dryer at a vacuum degree of -48°C and 20 Pa to obtain the gradient electromagnetic shielding aerogel framework.
[0083] Comparative Example 1
[0084] The printer parameters and printing steps are carried out according to Example 1. The gradient electromagnetic shielding aerogel framework is divided into three gradients and realized from the printer upwards. The concentration and pore gradients are 1:8:1, 1:8:1, 1:8:1 and 0.6 mm, 0.6 mm, 0.6 mm. The printed samples are all immersed in calcium chloride solution, placed in a refrigerator at -4°C for freezing, and then freeze-dried in a vacuum freeze dryer at a vacuum degree of -48°C and 20 Pa to obtain the gradient electromagnetic shielding aerogel framework.
[0085] Experimental Example 1: Gigahertz Electromagnetic Shielding Experiment
[0086] The gradient electromagnetic shielding aerogel frameworks prepared in Examples 1-4 and Comparative Example 1 are 3D printed into the size of a waveguide cavity suitable for a vector network analyzer, and then fixed in the waveguide cavity of the vector network analyzer. Under the radiation of electromagnetic waves with a frequency of 8.2-12.4 gigahertz, the S parameters before and after the transmission of electromagnetic waves are measured, and the electromagnetic shielding efficiency is calculated from the S parameters.
[0087] Figure 9 The electromagnetic shielding performance test and electromagnetic stealth performance test are carried out for the gradient electromagnetic shielding aerogel frameworks prepared in Examples 1-2. The test results show that the electromagnetic shielding efficiency of Example 1 is greater than 100 dB, and it can shield more than 99.99999999% of electromagnetic wave radiation, proving its excellent electromagnetic shielding performance.
[0088] At the same time, the reflection efficiency is as low as 2.45 dB, and the reflection coefficient is as low as 0.42, which can hide more than 58% of electromagnetic wave radiation, proving its good electromagnetic stealth performance and low reflection characteristics, and avoiding secondary electromagnetic radiation pollution. In contrast, Example 2 has a high reflection efficiency, proving that the concentration gradient from low to high concentration and the pore gradient from large to small have lower reflection characteristics.
[0089] Figure 10 The electromagnetic shielding performance test and electromagnetic stealth performance test are carried out for the electromagnetic shielding aerogel frameworks prepared in Examples 3-4. The test results show that Example 3 has lower reflection characteristics than Example 4, proving that the ability of the concentration gradient from low to high concentration to resist electromagnetic wave reflection is stronger.
[0090] Figure 11 For the electromagnetic shielding performance test and electromagnetic stealth performance test prepared in Example 1, Example 3 and Comparative Example 1, the test results show that the simultaneous presence of concentration and pore gradients can endow the electromagnetic shielding aerogel framework with more excellent shielding performance and low reflection characteristics, and Example 1 has the optimal electromagnetic shielding performance with low reflection characteristics.
[0091] Experimental Example 2: Actual electromagnetic shielding simulation
[0092] Place the gradient electromagnetic shielding aerogel framework prepared in Example 1 on the induction module of the microwave radar sensor, and observe the change of the induction light when the model car approaches the microwave radar sensor.
[0093] Place the gradient electromagnetic shielding aerogel framework prepared in Example 1 on the wireless magnetic charger, and observe the charging situation when the smartphone is placed on the charger.
[0094] Figure 13 (a) shows the actual electromagnetic shielding simulation test of the gradient electromagnetic shielding aerogel framework prepared in Example 1 with respect to the microwave radar sensor. When no object or sponge block is placed on the induction module and the model car approaches the microwave radar sensor, the induction light lights up; when the gradient electromagnetic shielding aerogel framework prepared in Example 1 is placed on the induction module and the car approaches the microwave radar sensor, the induction light has no reaction. It proves that the gradient electromagnetic shielding aerogel framework prepared in Example 1 has excellent electromagnetic shielding performance.
[0095] Figure 13 (b) shows the actual electromagnetic shielding simulation test of the gradient electromagnetic shielding aerogel framework prepared in Example 1 with respect to wireless magnetic charging. When paper or cellulose nanofiber material is placed on the charger, the phone can quickly show that it is in the charging state when placed on it; when the gradient electromagnetic shielding aerogel framework prepared in Example 1 is placed on the charger, the phone cannot be charged when placed on it. It proves that the gradient electromagnetic shielding aerogel framework prepared in Example 1 has excellent electromagnetic shielding performance.
[0096] Experimental Example 3: Photothermal performance test
[0097] Place Example 1 on a plane, and irradiate the gradient electromagnetic shielding aerogel framework with sunlight of different intensities and 808 nm near-infrared laser, and monitor the change of the surface temperature with an infrared thermal imager (FLIR A325SC camera).
[0098] Figure 14This is the graph of the solar photothermal test results for Example 1. It can be seen from the graph that under the irradiation of sunlight, the maximum temperature of the gradient electromagnetic shielding aerogel framework in Example 1 can reach about 70.1 degrees Celsius. In addition, it also shows good stability in the cyclic light irradiation experiment, indicating good solar photothermal performance and stability.
[0099] Figure 15 This is the graph of the 808nm near-infrared laser photothermal test results for Example 1. It can be seen from the graph that under the irradiation of the 808nm near-infrared laser, the maximum temperature of the gradient electromagnetic shielding aerogel framework in Example 1 can reach about 164.5 degrees Celsius. In addition, it also shows good stability in the cyclic heating and cooling light irradiation experiment, indicating good 808nm near-infrared laser photothermal performance and stability.
[0100] Experimental Example 4: De-icing and high-temperature infrared stealth experiment
[0101] Place Example 1 on a plane, then place the ice cubes on the gradient electromagnetic shielding aerogel framework prepared in Example 1, and apply continuous irradiation of 2 sunlights. Use an infrared thermal imager (FLIR A325SC camera) to monitor the change of the surface temperature at different time intervals.
[0102] Place Example 1 on a tank model heated to above 80 degrees Celsius to simulate a device working at high temperature, and use an infrared thermal imager (FLIR A325SC camera) to monitor the change of the surface temperature.
[0103] Figure 16 (a) This is the infrared thermal image of the ice melting situation of Example 1 at different time intervals under continuous irradiation of 2 sunlights. It can be seen that as time goes by, the ice cubes gradually melt. At 240s, the ice cubes have completely melted, proving good photothermal conversion performance.
[0104] Figure 16 (b) This is the infrared thermal imaging image of Example 1 covering the model of the device operating at high temperature. It can be seen that when there is no object covering the tank model, the surface temperature is very different from the surrounding environment; when the gradient electromagnetic shielding aerogel framework prepared in Example 1 covers the tank model, the surface temperature of the framework is similar to the ambient temperature, and the purpose of infrared stealth can be achieved. The de-icing and high-temperature infrared stealth experiments prove that the aerogel also has excellent photothermal conversion ability and can realize multi-scenario adaptive applications to effectively protect the equipment in military exploration. The above characteristics make it have great application potential in the fields of multi-scenario adaptable electromagnetic shielding composites, high-temperature stealth and anti-freezing materials, and military communication.
[0105] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art within the technical scope disclosed by the present invention can easily think of changes or substitutions, which should all be covered within the protection scope of the present invention. Therefore, the protection scope of the present invention should be subject to the protection scope of the claims.
Claims
1. An electromagnetic shielding aerogel framework with a concentration gradient and a pore gradient structure, wherein the aerogel framework has a multi-level concentration gradient and a pore gradient structure in the thickness direction, and each level of the gradient structure of the aerogel framework is composed of cellulose nanofibers (CNFs), MXene and poly (3,4-ethylenedioxythiophene) -polystyrene sulfonic acid (PEDOT:PSS) in different proportions.
2. The electromagnetic shielding aerogel framework according to claim 1, characterized in that: The multi-level concentration gradient and pore gradient of the aerogel framework are at least a three-level gradient structure.
3. The electromagnetic shielding aerogel framework according to claim 2, characterized in that: In the three-level gradient of the aerogel framework, the ratio of MXene and cellulose nanofiber content in each concentration gradient from bottom to top in the thickness direction remains the same, the content of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid is different, and the weight ratio of cellulose nanofiber:MXene:(PEDOT:PSS) is 1:8:1.5 to 1:8:4, 1:8:0.5 to 1:8:1.2, 1:8:0 to 1:8:0.1, preferably 1:8:1.8 to 1:8:2.2, 1:8:0.8 to 1:8:1.1, 1:8:0 to 1:8:0.05, and more preferably 1:8:2, 1:8:1, 1:8:0; wherein 1:8:0 means that PEDOT:PSS is not added.
4. The electromagnetic shielding aerogel framework according to claim 2, characterized in that: In the three-level gradient of the aerogel framework, each pore gradient from bottom to top in the thickness direction is 0.8 to 2.0 mm, 0.3 to 0.7 mm, 0.05 to 0.25 mm, preferably 0.8 to 1.5 mm, 0.45 to 0.65 mm, 0.10 to 0.20 mm, and more preferably 1.0 mm, 0.6 mm, 0.2 mm.
5. The method for preparing the electromagnetic shielding aerogel framework according to any one of claims 1 to 4, wherein the preparation method is based on 3D printing technology and comprises the following steps: 1) Preparation of MXene precipitate Dissolve 1 part by weight of LiF in 20 parts by weight of 9M hydrochloric acid, then add 1 part by weight of Ti3AlC2 powder and stir at 35°C for 48 hours; the suspension obtained after the reaction is centrifuged at 3500r / min×5min, washed with deionized water until the supernatant PH is ≥5, and the supernatant is poured out; the obtained multilayer MXene compound precipitate is dispersed and added to 25 parts by weight of deionized water, ultrasonicated in an ice bath for 1 hour, and then at 3500r / min×60min, the bottom MXene precipitate is recovered and concentrated, and high-speed centrifuged at a speed of 10,000r / min for 1 hour to obtain a MXene precipitate; 2) Preparation of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS) Under stirring conditions, 2 parts by weight of poly(sodium 4-styrene sulfonate) and 2 parts by weight of 3,4-ethylenedioxythiophene were added to 400 parts by weight of deionized water and stirred at room temperature for 15 minutes; then 5 parts by weight of sodium persulfate and 0.01 parts by weight of anhydrous ferric chloride were slowly added to the above mixture to initiate polymerization, and the mixture was fully stirred in an ice bath for 24 hours. As the reaction proceeded, the mixture changed from light blue to dark blue. After the reaction was terminated, the liquid was washed 3 times with water / methanol at a volume ratio of 1:1 to remove unreacted 3,4-ethylenedioxythiophene, and then washed 3 times with deionized water. The obtained sediment was frozen at -4°C, and then freeze-dried in a vacuum freeze dryer at -48°C and a vacuum degree of 20Pa to obtain PEDOT:PSS powder; 3) Preparation of 3D printing ink 5 parts by weight of the MXene precipitate with a weight percentage of 22.4% obtained in the above step 1) is added with 14 parts by weight of 1% cellulose nanofibers in a mortar and ground evenly, and the PEDOT:PSS powder is redispersed with a deionized water / dimethyl sulfoxide mixture with a volume ratio of 85:15, and then the PEDOT:PSS powder is added to the above mixture at a weight ratio of cellulose nanofiber:MXene:(PEDOT:PSS) of 1:8:0, 1:8:1, and 1:8:2 respectively and completely ground to form a 3D printing ink, wherein 1:8:0 means that no PEDOT:PSS is added; 4) Preparation of gradient electromagnetic shielding aerogel framework The three mixed inks obtained in the above step 3) are loaded into a syringe and left to stand at room temperature to remove bubbles. The geometric pattern required for printing is pre-designed and drawn through computer-aided design software, the motion path file of the printer nozzle is exported through slicing software, and the data is imported into a straight writing 3D printer. Finally, the ink is extruded from the nozzle to form filaments, and stacked layer by layer through the three-axis control of the printer, and the pore size is controlled by controlling the operating parameters of the 3D printer.
6. The method according to claim 5, characterized in that The printing movement speed is preferably 16.5-22.5 mm / s, and more preferably 19.5 mm / s.
7. The method according to claim 5, characterized in that The inner diameter of the printing nozzle is preferably 230-640 μm, and more preferably 460 μm.
8. The method according to claim 5, characterized in that The printing ink extrusion feed rate is preferably 14-18 mL / hr, more preferably 16 mL / hr.
9. A low-reflection electromagnetic shielding device, wherein the low-reflection electromagnetic shielding device is prepared from the electromagnetic shielding aerogel framework according to any one of claims 1 to 4.
Citation Information
Cited By
Anisotropic heterogeneous pore double-layer composite aerogel and preparation method thereof
CN122340792A